The prevalence of badnaviruses in West African yams (Dioscorea cayenensisrotundata) and evidence of endogenous pararetrovirus sequences in their genomes - Seal, S.; Turaki, A.; Muller, E.; Kumar, P. Lava; Kenyon, L.; Filloux, D.; Galzi, S.; López Montes, Antonio José; Iskra Caruana, M.L. (Elsevier, 2014)
Yam (Dioscorea spp.) is an important vegetatively-propagated staple crop in West Africa. Viruses arepervasive in yam worldwide, decreasing growth and yield, as well as hindering the international move-ment of germplasm. Badnaviruses have been reported to be the most prevalent in yam, and genomesof some other badnaviruses are known to be integrated in their host plant species. However, it was notclear if a similar scenario occurs in Dioscorea yam. This study was conducted to verify the prevalence ofbadnaviruses, and determine if badnavirus genomes are integrated in the yam genome.Leaf samples (n = 58) representing eight species of yam from global yam collections kept at CIRAD,France, and 127 samples of D. rotundata breeding lines (n = 112) and landraces (n = 15) at IITA, Nigeria,were screened using generic badnavirus PCR primers. Positive amplification of an expected ca. 579 bpfragment, corresponding to a partial RT-RNaseH region, was detected in 47 (81%) of 58 samples ana-lysed from CIRAD collections, and 100% of the 127 IITA D. rotundata samples. All the D. cayenensis and D.rotundata samples from the CIRAD and IITA collections tested PCR-positive, and sequencing of a selectionof the PCR products confirmed they were typical of the genus Badnavirus. A comparison of serolog-ical and nucleic acid techniques was used to investigate whether the PCR-positives were sequencesamplified from badnavirus particles or putative endogenous badnavirus sequences in the yam genome.Protein A sandwich-enzyme-linked immunosorbent assay (PAS-ELISA) with badnavirus polyclonal antis-era detected cross-reacting viral particles in only 60% (92 of 153) of the CIRAD collection samples analysed,in contrast to the aforementioned 81% by PCR. Immunosorbent electron microscopy (ISEM) of virus prepa-rations of a select set of 16 samples, representing different combinations of positive and negative PCRand PAS-ELISA results, identified bacilliform particles in 11 of these samples. Three PCR-positive yamsamples from Burkina Faso (cv. Pilimpikou) were identified in which no viral particles were detected byeither PAS-ELISA or ISEM. Southern hybridisation results using a yam badnavirus RT-RNaseH sequence(Gn155Dr) as probe, supported a lack of badnavirus particles in the cv. Pilimpikou and identified theirequivalent sequences to be of plant genome origin. Probe Gn155Dr, however, hybridised to viral particlesand plant genomic DNA in three D. rotundata samples from Guinea. These results represent the first datademonstrating the presence of integrated sequences of badnaviruses in yam. The implications of this forvirus-indexing, breeding and multiplication of seed yams are discussed.